ChemInform Abstract: Palladium‐Catalyzed Desulfitative Cross‐Coupling of Sodium Arylsulfinates with Aryl Bromides and Chlorides: An Alternative Convenient Synthesis of Biaryls. Issue 10 (11th March 2014) - Zhou, Chao; Li, Yaming; Lu, Yang; Zhang, Rong; Jin, Kun; Fu, Xinmei; Duan, Chunying
Abstract The title reaction proceeds under relatively mild reaction conditions without the need for additives, base or co‐catalyst.